Kan våra studenter svenska? - Martin Lennart Malmström (Educare)
There is a popular discourse in Sweden describing student writing as defective. Entering the discourse about the state and possible change of student writing, this paper analyses the writing part of the national test in Swedish for upper secondary school. Student texts from 1976, 1986, 1996, 2005, and 2012 are investigated both quantitatively and qualitatively. Drawing on Hultman and Westman (1977) for the quantitative analysis, the paper examines nominals (in particular, the use of nouns and pronouns), and correctness (distinguishing between different kinds of mistakes). The qualitative analysis pertains to the rhetoric competence in student essays. The results show that the student texts have become somewhat more informal, or speech-like, over the years. The study also indicates that the number of mistakes has increased slightly, especially the grave mistakes, which may make the texts difficult to comprehend. On the other hand, the rhetoric competence of today’s students seems, comparatively, good. The popular discourse, then, is right in some respects, but the situation is more nuanced than the critics claim.